Phase equilibria of size- and charge-asymmetric primitive models of ionic fluids: the method of collective variables - Patsahan, O.V.; Patsahan, T.M. (Condensed Matter Physics, 2010)
We study the phase diagrams of z:1 size-asymmetric primitive models (PMs) using a theory that exploits the method of collective variables. Based on the explicit expression for the relevant chemical potential (conjugate to the order parameter) which includes the correlation effects up to the third order we consider some particular cases of asymmetric PMs (1:1, 2:1 and 3:1 systems). Coexistence curves and critical parameters are calculated as functions of size ratio λ=σ+/σ-. Similar to simulations, our theory predicts the reduction of coexistence regions as well as a decrease of critical parameters Tc* and ρc* with an increase of size asymmetry.